Purple passion fruit - Muñoz, Katalina; Londoño, Julián; Sepulveda, Stella; Gómez, Melisa; Tabares, Ana Isabel; Carvalho, Catarina P.P. (Grupo de alimentos y marcas Nutresa, 2025)
The purple passion fruit is native of southern Brazil through Paraguay to northern Argentina and was thoroughly dispersed during the 19th century to other countries in South America, Caribe, Asia, Africa, India and Australia. Passion fruit is adapted today throughout the tropics and subtropics and has naturalized and escaped in many areas including North America, many islands of the Pacific Ocean, Australia, New Zealand, South Africa and SE Asia (Morton, 1987).